2021
DOI: 10.1177/1066896920988359
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Ciliated Muconodular Papillary Tumors of the Lung: A Case Report

Abstract: Ciliated muconodular papillary tumors (CMPTs) are rare peripheral lung lesions, characterized by papillary architecture and ciliated columnar cells admixed with mucous cells and basal cells. Only about 50 cases have been reported to date and is categorized as a benign neoplasm. In this article, we report an extremely rare case of 79-year-old man with a CMPT that developed in his right upper lobe. The central region of the tumor showed features of classic CMPT, while marginal area of the tumor showed the charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…Four previous publications reported patients who had BA/CMPT with malignant transformation (Table 1 )[ 2 - 5 ]. Miyai and collaborators[ 2 ] presented a case of CMPT with malignant transformation of basal cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Four previous publications reported patients who had BA/CMPT with malignant transformation (Table 1 )[ 2 - 5 ]. Miyai and collaborators[ 2 ] presented a case of CMPT with malignant transformation of basal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Han and co-workers[ 4 ] presented a unique case with loss of the continuous basal cell layer at the junction between BA and IMA, although the BA and IMA had the same KRAS mutations. Wang et al [ 5 ] also described a patient with malignant CMPT. We used H&E staining and immunohistochemistry to diagnose our patient as having MA caused by the malignant transformation of BA, thus providing histological evidence of the malignant potential of BA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is still controversial whether BA has malignant potential. More and more cases with malignant transformation have been reported in the literature recently (3)(4)(5)7). Miyai et al(3) reported a case of CMPT with malignant transformation of basal tumor cell components, and Chen et al (7) descripted a case of mucinous adenocarcinoma caused by cancerization from CMPT and speculated CMPT is a precancerous lesion of mucinous adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…According to the proposal by Chang et al (1), the uni ed histological characteristic of BA is bilayered bronchiolar-type proliferation with a continuous layer of basal cells, which is considered to be the basis for BA identi ed as a benign tumor histologically. However, because of its rarity and potential malignant changes reported recently in few cases (2)(3)(4)(5), the biological potential of BA remains controversial and unclear. Herein, we report a rare case of multiple BAs with malignant transformation and CCNE1(cyclin E1)mutation, to increase the understanding of this disease and reduce missed diagnosis.…”
Section: Introductionmentioning
confidence: 99%